Energetic and proteic characterization of prime sources of animal origin used in the formulation of a balanced feed for dairy cattle. - Boschini-Figueroa, Carlos (2005)
The kinetics of ruminaldegradation of dry matter, crude protein and ether extract weredetermined for fish, meat and bone, and poultry meals. Thesemeals of animal origin showed characteristics proper of thespecies of origin, not only in the soluble fraction but also inthe rates of ruminal degradability of the potentially degradablefraction. Based on the results of degradation after 48 hours ofruminal incubation, the true digestible contents of the proteinand the digested ether extract were determined biologically,making the measurement of the total digestible nutrients, andthe concentration and net rate of digestible energy and feed,more precise than determinations by chemical methods. Theconcentrations of energy for milk production was 2.02, 1.66,and 2.60 Mcals/kg for fish, meat and bone, and poultry meals,respectively. The fraction of soluble protein (A) was high infish meal (75.29%), intermediate in meat and bone (46.83%),and low in poultry (25.75%), with a degradable fraction (B) of10.62, 27.66, and 42.06%, along with an insoluble fraction (C)of 14.09, 25.51, and 32.19%, respectively. The degradedprotein in the rumen was 83.23, 66.25, and 51.98% in thesame order cited above. The contents of crude proteineffectively retained by the animals during the whole digestiveprocess were 53.29, 51.86, and 42.05% for fish, meat andbone and poultry meals, respectively.